A comparative molecular dynamics and NMR study of H2-Db complex with a Sendai virus antigen reveals the high plasticity of the bound peptide. (October 2022) - Papakyriakou, Athanasios; Scherer, Eva; Bailey, Alistair; Elliott, Tim; Werner, Jörn
Abstract : It has been recognized that different peptides can influence the dynamics of the peptide-loaded MHC-I complex, which plays a pivotal role to CTL recognition and cross reactivity. To gain a deep understanding of the relationship between the peptide-bound MHC-I structure and dynamics we have performed Molecular Dynamics simulations (MDs) of the Sendai virus antigen FAPGNYPAL bound to the mouse allele H2-Db complex with human β2m for an aggregate simulation time of 100 μs. Our MDs predict that the antigenic peptide samples several conformational states with partially dissociated N- and C-termini, mainly as a result of the antigen-binding groove side chain dynamics. These data have been correlated with an NMR study of H2-Db loaded with a series of 13C-labelled FAPGNYPAL and modified pep- tides, which confirmed that the bound peptides sample multiple conformational states. Interestingly, this comparative analysis revealed that peptide dynamics comprising partially dissociated states is not accompanied by large conformational changes of the main chain atoms at the peptide-binding groove of the MHC-I.